Scrub Typhus Pathogenesis: Innate Immune Response and Lung Injury During Orientia tsutsugamushi Infection - Trent, Brandon; Fisher, James; Soong, Lynn (Frontiers in Microbiology, 2019)
Scrub typhus is an understudied, potentially lethal disease caused by infection with the bacterium Orientia tsutsugamushi. Despite causing an estimated one million cases per year and an increasing global presence, mechanisms of scrub typhus disease pathogenesis remain unclear. One of the most life-threatening conditions that can arise in human scrub typhus patients is acute respiratory distress syndrome (ARDS). Tissue damage and organ failure during ARDS are a complex process with such hallmarks as damage to lung vasculature and prolonged recruitment of inflammatory immune cells to the lung, developments also observed in humans and animal models of O. tsutsugamushi infection. Although many different cell types in the lung contribute to ARDS development, in this review we specifically highlight what is known during O. tsutsugamushi infection regarding pulmonary endothelial activation and damage well as the recruitment and roles of neutrophils and macrophages in the lung. Continued investigation of the lung microenvironment and cellular interactions will be beneficial to elucidate ARDS development and possible treatment during scrub typhus.